Comparing the accuracy of positive and negative indocyanine green staining in guiding laparoscopic anatomical liver resection: protocol for a randomised controlled trial - Malek Abdallah Muflih Alomari; Taiga Wakabayashi; Marco Colella; Yoshiki Fujiyama; Ebaa Ababneh; Go Wakabayashi; Kohei Mishima (BMJ Open)
Introduction Knowledge of the clinical liver anatomy has evolved with advanced imaging modalities and laparoscopic surgery. Therefore, precise anatomical resection knowledge has become the standard treatment for primary and secondary liver cancer. Segmentectomy, a parenchymal-preserving approach, is regarded as an option for anatomical resections in patients with impaired liver. Indocyanine green (ICG) staining is a promising method for understanding the anatomical borders of the liver segments. There are two methods of ICG staining (positive and negative), and the superiority of either approach has not been determined to date.Methods and analysis This is a prospective randomised controlled superiority clinical trial performed in a single centre tertiary hospital in Japan. A comparison between the accuracy of positive and negative ICG staining in guiding laparoscopic anatomical liver resection is planned in this study. Possible candidates are patients with liver malignant tumours in whom laparoscopic monosegmentectomy or subsegmentectomy is planned. Fifty patients will be prospectively allocated into the following two groups: group A, ICG-negative staining group, and group B, ICG-positive staining group. The optimal dose of ICG for positive staining will be determined during the preparation phase. To assess the ability of the ICG fluorescence guidance in anatomical resection, the primary endpoint is the success rate of ICG staining, which consists of a subjective optical scoring (SOS) based on three components: superficial demarcation in the liver surface, visualisation of the parenchymal borders and consistency with the preoperative three-dimensional simulation. The secondary endpoints are the evaluation of short-term surgical outcomes and recurrence-free survival.Ethics and dissemination The study was approved by Ageo Central General Hospital Clinical Research Ethical Committee (No: 1044) and it carried out following the Declaration of Helsinki (2013 revision). Informed consent will be taken from the patients before participating. The findings will be disseminated through peer-reviewed publications, scientific meetings and conferences.Trial registration number UMIN000049815.